Phase Transitions at the Temperatures Below 0°C in Mixtures of Cell Suspensions with Human Placental Extract Fractions - Zinchenko, A. V.; Govorova, Yu. S.; Bobrova, E. N. (Problems of Cryobiology and Cryomedicine, 2024)
Using differential scanning calorimetry the phase transitions at the temperatures below 0°Cin fractions of extracts derived from human placenta with molecular mass up to 5; 50–70 and 750 kDa, as well as in suspensions of red blood cells and the yeasts Saccharomyces cerevisiae supplemented with the mentioned fractions of extracts were studied. General regularities of the influence of cells on low-temperature phase transitions in the fractions of extracts were revealed. A significant reduction in the intensities of the inversion peak and the eutectic melting peak was found likely due to the presence of NaCl. These phenomena are likely caused by the changed intermolecular interactions in the liquid phase as a result of competition between active centers of organic molecules for binding the water molecules. Reduced intensity of low-energy process of inversion, caused by conformational change in molecules of the fractions in the presence of cells, result from interactions of molecules involved in the process of inversion with the cells.